Ultrasound Parameters Of Hip Displasya In Children Under One Year Old - Shirov, Bobur Furkatovich; Mardieva, Gulshad Mamatmuradovna (Journal of Neonatal Surgery, 2025)
Developmental dysplasia of the hip (DDH) is a prevalent pediatric orthopedic condition characterized by abnormal development of the hip joint, ranging from mild instability to complete dislocation. Early diagnosis and intervention are critical for preventing long-term functional limitations, gait abnormalities, and degenerative joint diseases. In recent decades, ultrasonography has emerged as the primary diagnostic modality for screening and evaluating hip development in infants, particularly those under one year of age, due to its non-invasive nature, lack of radiation, and ability to visualize cartilaginous structures. This study aims to comprehensively examine the key ultrasound parameters that aid in diagnosing hip dysplasia in children less than 12 months old. Utilizing Graf’s classification system—the most widely accepted sonographic method for evaluating infant hips—we focused on measuring the alpha and beta angles, which reflect the bony roof and cartilaginous coverage of the acetabulum, respectively. Additionally, the percentage of femoral head coverage and hip joint morphology were assessed to establish a correlation between sonographic findings and clinical risk factors such as breech presentation, family history, and female sex. A prospective analysis was conducted on 150 infants (85 females and 65 males) between the ages of 0 and 12 months who were referred for hip screening at a pediatric diagnostic center. All patients underwent bilateral hip ultrasonography performed by experienced sonographers trained in the Graf technique. Results were categorized according to the Graf classification (types I to IV), with particular attention paid to borderline cases (type IIa and IIb), which require close monitoring and potential early intervention. The findings revealed that alpha angle measurement remains the most reliable indicator of hip maturity, with a value ≥60° considered normal (type I). In contrast, beta angles and femoral head coverage percentages showed variation in borderline and dysplastic hips. Notably, a higher prevalence of type IIb and IIc hips was observed in female infants and those with positive family history. Follow-up scans confirmed the utility of serial ultrasound in monitoring hip development and guiding treatment decisions, such as the application of the Pavlik harness. Our results support the implementation of universal or targeted ultrasound screening protocols in early infancy to identify and manage DDH effectively. Furthermore, the study underscores the importance of training healthcare providers in accurate ultrasound technique and interpretation to reduce misdiagnosis and improve outcomes. In conclusion, ultrasonography remains an essential tool in the early detection and classification of hip dysplasia in infants. The use of standardized parameters such as alpha and beta angles, alongside thorough clinical evaluation, can significantly improve the prognosis of affected children. Timely intervention based on precise sonographic findings ensures normal hip joint development and prevents future orthopedic complications.